The Origins of Reinforced Concrete Interventions to Historic Structures in Turkey - İNAN OCAK, ZEYNEP (My University, 2024)
Reinforced concrete interventions have been a critical issue for restorations in the field of conservation since the early twentieth century. Until the twenty-first century, cement-containing interventions could be seen in almost all restorations in Turkey. There are even examples of monumental buildings whose structural systems have been converted to reinforced concrete. However, in more recent years in Turkey, reconstructions with echoes of stylistic unity began to emerge, with less of a focus on preservation and without consideration of the documentary value of the reinforced concrete used in the strengthening interventions of the twentieth century. From a structural viewpoint, it is necessary to assess whether mixed structures of reinforced concrete and masonry work well. From a conservation viewpoint, despite negative perceptions of reinforced concrete, these historic interventions have avoided confusion or falsification where the precise original nature of the structure is unknown. With these remarks in mind, this study describes the origins of reinforced concrete interventions in conservation in Turkey. It provides a general framework of the concept of interventions for strengthening and preservation at the intersection of reinforced concrete, earthquakes, codes, and conservation theories by tracking experiences with reinforced concrete from the Ottoman Empire to the early years of the Republic of Turkey.
Keywords: Sosyal ve Beşeri Bilimler; Sanat; İç Mimarlık; Social Sciences and Humanities; Art; Interior Architecture; Sanat Ve Beşeri Bilimler (Ahci); Sanat Ve Beşeri Bilimler; Mimari; Arts & Humanities (Ahci); Arts & Humanities; Architecture; Koruma; Sosyal Bilimler ve Beşeri Bilimler; Fizik Bilimleri; Görsel Sanatlar ve Gösteri Sanatları; Conservation; Social Sciences & Humanities; Physical Sciences; Visual Arts and Performing Arts; construction history; earthquakes; reinforced concrete; restoration, consolidation; Turkey